Evaluation Of The Implementation Of Elementary Teacher Certification Policies Through Teacher Professional Education Programs In Gorontalo City - Warni Tune Sumar; Ansar Ansar (International Journal Labs, 2024)
This study aims to comprehensively evaluate the implementation of the elementary school teacher certification policy through the teacher professional education program in Gorontalo City from four different aspects. The evaluation shows that in terms of context, the implementation of this policy is considered very good with an achievement of 92%, which is in accordance with the Standard Operating Procedures as the organizer of PPG activities. In addition, in terms of input, the evaluation showed excellent results with a percentage of 97%, supported by the availability of adequate Human Resources and the qualifications of instructors in accordance with government requirements. In terms of process, the study found excellent performance with an achievement of 95%, showing that PPG activities were carried out in accordance with the SOP set by the Ministry of Research, Technology and Higher Education. On the product side, the evaluation showed excellent results with a percentage of 93%, emphasizing that a well-organized process in implementing the PPG program contributed to the quality of the final product produced. Overall, these findings confirm that the teacher certification policy through the teacher professional education program in Gorontalo City has been successfully implemented from all aspects evaluated, providing an important view for the development of future education policies and the importance of compliance with operational standards to achieve optimal results in teacher professional education.